Religion Helps Migrants: Roman Catholic Church and the Migrant Crisis During the Pontificate of Pope Francis - A. Szabaciuk (Международная аналитика, 2021)
This essay evaluates the standpoint that the Roman Catholic Church has adopted regarding the European migrant crisis. Some countries feel a severe outfl ow of people due to mass labor migration; others must deal with the challenges as transit states, and others – enormous challenges generated by the infl ux of economic immigrants and refugees. The most popular theories of migration and public policies very often ignore the ethical component of migration. One of the entities that constantly emphasizes the humanitarian aspect of migration is the Holy See. Popes, beginning with Leo XIII, have repeatedly raised the issue of rights to a dignifi ed life and decent work, and if it is necessary also to migrate in search of a safe shelter and a better life. Pope Francis, like his predecessors, referring to the problem of migration, puts people fi rst. He emphasizes that all migration streams consist of individuals who deserve respect and care because we see in them the face of God. This paper concludes that the Church remains the signifi cant international body impartial amidst the growing European schism on the migrant issue.